2009
DOI: 10.1007/s00436-009-1593-8
|View full text |Cite
|
Sign up to set email alerts
|

Oviposition-deterrent, ovicidal, and repellent activities of indigenous plant extracts against Anopheles subpictus Grassi (Diptera: Culicidae)

Abstract: Insecticides of botanical origin may serve as suitable alternative biocontrol techniques in the future. The leaf acetone, ethyl acetate, and methanol extracts of Aegle marmelos (Linn.) Correa ex Roxb, Andrographis lineata Wallich ex Nees, and Cocculus hirsutus (L.) Diels were tested for oviposition-deterrent, ovicidal, and repellent activities against Anopheles subpictus Grassi (Diptera: Culicidae). The percentage of effective oviposition repellency of 92.60 , 93.04, 95.20, 88.26, 92.80, 94.01, 95.77, 96.93, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(55 citation statements)
references
References 44 publications
(46 reference statements)
5
49
0
1
Order By: Relevance
“…aegypti mosquitoes. The results are comparable with an earlier report by Elango et al [30] that the maximum repellent activity was observed at 500 ppm in methanol extracts of Aegle marmelos, Acacia lineata, and ethyl acetate extract of Chamaecytisus hirsutus, and the mean complete protection time ranged from 90 to 120 min against Anopheles subpictus. The hexane extract of Andrographis paniculata was more effective in exhibiting the repellent action against the mosquito as compared with Acacia lineate extract and the complete protections was observed for 150 min in hexane extract of Andrographis paniculata at 500 ppm against Culex tritaeniorhynchus bites [31] .…”
Section: Discussionsupporting
confidence: 91%
“…aegypti mosquitoes. The results are comparable with an earlier report by Elango et al [30] that the maximum repellent activity was observed at 500 ppm in methanol extracts of Aegle marmelos, Acacia lineata, and ethyl acetate extract of Chamaecytisus hirsutus, and the mean complete protection time ranged from 90 to 120 min against Anopheles subpictus. The hexane extract of Andrographis paniculata was more effective in exhibiting the repellent action against the mosquito as compared with Acacia lineate extract and the complete protections was observed for 150 min in hexane extract of Andrographis paniculata at 500 ppm against Culex tritaeniorhynchus bites [31] .…”
Section: Discussionsupporting
confidence: 91%
“…stephensi. respectively [18]. In conclusion, the present study clearly proved that the efficacy of leaf and seed extracts of P. dulce can be suggested as a repellent agent against An.…”
Section: Resultssupporting
confidence: 69%
“…Not surprisingly, these plants were found to be deterrent for mosquito oviposition , Elango et al 2009, Rajkumar and Jebane san 2009, Warikoo et al 2011, showing that mosqui toes avoid conditions that are noxious to their offspring. However, suitability for the offspring does not always explain the oviposition effect of plant infusions; the water soluble lectin isolated from the Moringa oleifera Lamarck tree is larvicidal and ovicidal against Ae.…”
Section: Cues From Larval Foodmentioning
confidence: 99%
“…Other plants (such as Solenostemma argel Delile) have a negative effect on mosquito eggs , Elango et al 2009, Warikoo et al 2011 or larvae (Al Doghairi et al 2004, Rajkumar andJebane san 2009). Not surprisingly, these plants were found to be deterrent for mosquito oviposition , Elango et al 2009, Rajkumar and Jebane san 2009, Warikoo et al 2011, showing that mosqui toes avoid conditions that are noxious to their offspring.…”
Section: Cues From Larval Foodmentioning
confidence: 99%